IMPROVING THE ACHIEVEMENT OF LEARNING FRAGED MATERIALS METHEMATIC SUBJECTION USING MEDEM PLACES FOR IV GRADE STUDENTS OF STATE SD. 137957 TANJUNGBALAI STUDY YEAR 2017/2018 - Nazmi, Nazmi (Jurnal Sabilarrasyad, 2018)
This study aims to: 1) Determine whether the use of transparent glass plastic media and the demonstration method (Medem Plaque) can improve student learning outcomes in mathematics learning on fractions material in grade IV SD.Negri Number 137957 Tanjungbalai City. 2) Identifying problems that occur in the teaching and learning process of Mathematics in class IV State Elementary School Number 137957 Kota Tanjungbalai. This research method is a Classroom Action Research (Cassroom Action Research). The results of the study at the time of the initial test were 53.02 with learning completeness of 0%, but after taking action in the first cycle, the average learning outcomes were 77.5 where 17 students or 70.83% of students have reached the level of learning completeness (Total value of 70). total value 70). That the use of transparent glass plastic media and the demonstration method (Pla kat Medem) can increase students' reasoning to understand Mathematics lessons more easily and clearly because they are learned directly through experiments conducted by students themselves.